The Case of Childfree in Social Affairs: Analysis of Tafsir Al-Maraghī by Ahmad Musțafa Al-Maraghī - Isianah, Isianah (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
Childfree is the decision not to have children, originally emerging in the West and spreading to Indonesia, sparking debates with religious principles. The Tafsir Al-Maraghȋ highlights the purpose of partnering in Islam, emphasizing the sustainability of humanity. Verses such as An-Nahl 16:72, Ar-Rum 30:21, and Asy-Syura 42:11 underscore the importance of children's roles in the family. Research, utilizing library research methods and a descriptive analytical approach, indicates that the childfree decision can be positive if based on considerations that bring benefits. However, without a strong foundation or neglecting the core values of marriage, it is deemed inconsistent with religious teachings emphasizing the purpose of marriage to preserve human existence and the inherent nature of humanity.